Cyber Security Behaviorin Online Distance Learning: Utilizing National E-Learning Policy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This present study discovers cybersecurity awareness in online distance learning (ODL) during the pandemic crisis. ODL is an excellent way of teaching and learning during this catastrophe. The Government has imposed the National E-learning Policy to support ODL procedures. Unfortunately, the policies have not been carefully planned on security elements. Therefore, by utilizing Information Security Awareness Capability Model and Situation Awareness-Oriented Cyber Security Education Model, we able to: (1) design the security elements for National e-Learning Policy (2) develop a conceptual model of security behavior that benefits ODL procedure. Principally, four factors are demanding attention in the domain of cybersecurity features. On the other hand, there are partially supported hypotheses between the dimensions of cybersecurity and behaviour. Nutshell, we believe our paper is extending the body of knowledge in cybersecurity elements, awareness, and behaviour literature. Future direction, limitation, and conclusion have been thoroughly discussed.